Application of anti-money laundering measures during the investigation of crimes related to drug trafficking in Kazakhstan - Daurembekov Е.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
This article discusses the current problems of improving anti-money laundering measures in the investigation of crimes directly related to the illicit trafficking of narcotic drugs and psychotropic substances in Kazakhstan. The author highlights the organizational and legal aspects of the identification and further investigation of criminal offenses related to drug trafficking, as well as the criminalistic characterization of their sale and subsequent money laundering. The practical experience of law enforcement agencies and international organizations whose activities are aimed at suppressing money laundering and drug trafficking is being studied. Based on the analysis, the author concludes that it is necessary to develop systematic measures to combat money laundering in the legalization of criminal proceeds. A study is being conducted on the activities of the informal organization Egmont group in recent years, information on money laundering from drug trafficking. The purpose of the study is to identify effective measures to combat money laundering by examining statistical data and empirical evidence of crimes related to illicit trafficking in narcotic drugs and psychotropic substances. In studying this problem, various scientific research methods were used, which made it possible to objectively and comprehensively disclose certain provisions of the topic of the article. As a result of the conducted research, the author draws conclusions and suggests measures to counter money laundering in the shadow economy.